14th EBC Standard Malt 1997: Submitted on behalf of the EBC Analysis Committee - Hagen, W.; Benard, M. (BrewingScience, 1998)
The 14th Standard Malt has been accepted after analysis by the Analysis Committee of the European Brewery Convention and by European laboratories participating in the CERBIA monthly ring test. The malt can be used for checking the results of test methods described in Analytica EBC or for calibration of other methods (flow injection, near infrared reflectance etc.).